Miraculous recovery after severe coronavirus disease-19 in old age patient: A rare case Report - Madhulika Dubey,; Mohd. Mustahsin,; Garima Singh, (Indian Journal of Case Reports, 2021)
A novel severe acute respiratory syndrome coronavirus 2 led to an ongoing coronavirus disease (COVID)-19 pandemic since December 2019. It has affected all age groups; however, older adults are particularly susceptible to the virus and develop severe symptoms, and frequently require critical care admissions. They often require long-term home-based care and multidisciplinary rehabilitation programs. Here, we report a case of complete clinical recovery of a 74-year-old female with no post-COVID sequelae despite severe acute respiratory distress syndrome, multiple comorbidities, and the need for invasive mechanical ventilation. We believe that this case report can further guide the physicians to manage such critical cases.